Shiga toxin-producing Escherichia coli: incidence and clinical features in a setting with complete screening of patients with suspected infective diarrhoea. (June 2018) - Pedersen, R.M.; Nielsen, M.T.K.; Möller, S.; Ethelberg, S.; Skov, M.N.; Kolmos, H.J.; Scheutz, F.; Holt, H.M.; Rosenvinge, F.S.
Abstract: Objectives: Shiga toxin-producing Escherichia coli (STEC) causes diarrhoeal disease, bloody diarrhoea, and haemolytic uraemic syndrome. The aim of this study was to describe the incidence of STEC and the clinical features of STEC patients from a well-defined Danish population in which all fecal samples of patients with suspected infective gastroenteritis were analysed for STEC. Methods: In this population-based cohort study, all stool samples referred to two clinical microbiology laboratories were screened for STEC by culture and/or PCR. Epidemiological ( n =170) and clinical ( n =209) characteristics were analysed using data from local and national registries. Results: Overall, 75, 132 samples from 30, 073 patients were screened resulting in 217 unique STEC-isolates. The epidemiological analysis showed an incidence of 10.1 cases per 100, 000 person-years, which was more than twofold higher than the incidence in the rest of Denmark (3.4 cases per 100, 000 person-years, p <0.001). Three groups were associated with a higher incidence: age <5 years ( n =28, p <0.001), age ≥65 years ( n =38, p 0.045), and foreign ethnicity ( n =27, p 0.003). In the clinical analysis, patients with STEC harbouring only the Shiga toxin 1 gene ( stx 1 -only isolates) showed a lower frequency of acute ( n =11, p <0.05) and bloody diarrhoea ( n =5, p <0.05) and a higher frequency of gastrointestinal symptoms for ≥3 months ( n =8, p <0.05) than the other STEC patients. Conclusions: We report a more than twofold higher incidence in the project area compared with the rest of Denmark, indicating that patients remain undiagnosed when selective STEC screening is used. We found an association between patients with stx 1 -only isolates and long-term gastrointestinal symptoms.